2013
DOI: 10.1200/jco.2013.31.15_suppl.e12007
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 as a potential cancer stem cell marker in breast cancer.

Abstract: e12007 Background: The identification of cancer stem cell (CSC) markers gives opportunity to develop new target therapies. ABCG2 protein is reported as a predictive marker for breast cancer resistance to chemotherapy and as a potential marker for CSC in solid tumors. Methods: We included prospectively 41 patients with locally advanced or metastatic (LAMBC) invasive ductal carcinomas treated with NACT. The expression of CD44/CD24 and ABCG2 was analyzed by flow cytometry after fresh tumor sample digestion. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…BCSCs reportedly overexpress the ATP binding cassette (ABC) transporters such as the ABCB1/multi-drug resistance protein-1 (MDR1)/P-gp, ABC sub-family G-2 (ABCG2)/breast cancer resistance protein (BCRP), ABC sub-family C-1 (ABCC1)/multidrug resistance-associated protein 1 (MRP1), ABC sub-family C-3 (ABCC3), and ATP-binding cassette sub-family B-5 (ABCB5), all of which were implicated in the ability of BCSCs to resist drug interventions and trigger cancer relapse [ 185 ]. ABCG2/BCRP and ABCB1/MDR1/P-gp that efflux Hoechst 33342 dye are also used as a function of cell surface markers for chemoresistance in BCSCs [ 186 , 187 ].…”
Section: Role Of Bcscs In Chemoresistance In Breast Cancersmentioning
confidence: 99%
“…BCSCs reportedly overexpress the ATP binding cassette (ABC) transporters such as the ABCB1/multi-drug resistance protein-1 (MDR1)/P-gp, ABC sub-family G-2 (ABCG2)/breast cancer resistance protein (BCRP), ABC sub-family C-1 (ABCC1)/multidrug resistance-associated protein 1 (MRP1), ABC sub-family C-3 (ABCC3), and ATP-binding cassette sub-family B-5 (ABCB5), all of which were implicated in the ability of BCSCs to resist drug interventions and trigger cancer relapse [ 185 ]. ABCG2/BCRP and ABCB1/MDR1/P-gp that efflux Hoechst 33342 dye are also used as a function of cell surface markers for chemoresistance in BCSCs [ 186 , 187 ].…”
Section: Role Of Bcscs In Chemoresistance In Breast Cancersmentioning
confidence: 99%
“…In addition, studies have shown the functional relevance of ATP binding cassette subfamily G member 2 -ABCG2 (also known as BCRP, a breast cancer resistance protein) in relation to CSCs and therapeutic response. ABCG2 has been identified as a predictive marker of chemotherapy resistance and a potential CSC marker in solid tumors [5]. Resistance to cytotoxic agents has been attributed to the efflux of chemotherapeutic drugs by CSC-expressed ABCG2 [6].…”
Section: Introductionmentioning
confidence: 99%
“…SP cells have shown functions different from those of NSP cells and have been considered a substitute for CSCs, to some extent, in several studies (Dubrovska et al, 2012;Feng et al, 2015;Guo et al, 2016;Liao et al, 2015;Summer et al, 2003;Teshima et al, 2014;Van den Broeck et al, 2013;Wang et al, 2017;Zhao et al, 2016). Isolation of SP cells is typically based on their ability to pump out Hoechst 33342 dye given the high expression of adenosine triphosphate (ATP)-binding cassette (ABC) membrane transporters on their membranes (27, 28 Goodell, 2005;Patrawala et al, 2005), a characteristic of stem cells (Ding et al, 2010;Hu et al, 2017;Tiezzi et al, 2013). Further, SP cells cannot pump out Hoechst 33342 dye when verapamil, a calcium channel antagonist, is used to inhibit ABC membrane transporters, whereas the influence of verapamil on NSP cells is negligible (Scharenberg et al, 2002).…”
Section: Introductionmentioning
confidence: 99%